1976
DOI: 10.1136/bmj.1.6024.1520
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and early management of birth injuries to the brachial plexus.

Abstract: SummaryTwenty-four cases of birth injury to the brachial plexus were seen in 21 infants over 15 years. Obstetric complications were common, and in 11 cases traction was needed to deliver the shoulders. Three out of every four arms fully recovered after exercises. Splints were not needed. Reconstructive procedures were performed on three permanently paralysed arms when the children were aged about 4. There was no way of predicting which patients would recover. The muscles supplied by the suprascapular nerve wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
2

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 1 publication
0
30
0
2
Order By: Relevance
“…The validity of this somewhat arbitrary limit is borne out by reports describing a steady functional state after two to three years. 4,10,74,90 Only two authors reported ongoing recovery after this period, in sporadic cases. 102,107 Additionally, neurological examinations become more accurate as children get older because of their increased ability to cooperate.…”
Section: Follow-upmentioning
confidence: 99%
“…The validity of this somewhat arbitrary limit is borne out by reports describing a steady functional state after two to three years. 4,10,74,90 Only two authors reported ongoing recovery after this period, in sporadic cases. 102,107 Additionally, neurological examinations become more accurate as children get older because of their increased ability to cooperate.…”
Section: Follow-upmentioning
confidence: 99%
“…Obstetrical paralysis of the brachial plexus has been reported in 0.2-2.5% of births [Adler and Patterson, 1967;Bennet and Harrold, 1976;Gagnaireet al, 1975;Merger and Judet, 1973;Tan, 1973;Thoulon and Varnier, 1974;Vassal os et al, 1968]. It occurs in decreasing order of frequency as paralysis of the upper plexus, total paralysis and paralysis of the lower plexus.…”
Section: Introductionmentioning
confidence: 99%
“…The percent of spontaneous recovery var ies from 40 to 75% [Bennet and Harrold, 1976;Czurda andMeznik, 1977;Tan, 1973]. Some authors report an improvement or even complete recovery within the first weeks of life for most babies [Tan, 1973;Thoulon and Varnier, 1974], Sometimes, however, recovery, when it does occur is evi dent only at 1-1 'h' years of age [Adler and Patterson, 1967;Bennet and Harrold, 1976;Gordon et al, 1973].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations